Soil Investigation in Evergreen Forests of Western Ghats - Yadav, J. S. P.; Pathak, T. C.; Mahi, G. S. (Indian Forester, 1970)
The results of a soil investigation conducted in 1960 in some evergreen forests of Western Ghats in the States of Mysore, Madras and Kerala are described. The soils show wide variations in depth, texture, stoniness, moisture regime, drainage, topographical situation, etc., but in general they are formed in situ and are acidic in reaction, poor in bases and lateritic in nature with a fair supply of organic matter and nitrogen. The intensive mineral weathering and rapid turn over of the nutrients under the local conditions facilitate easy supply of the nutrients to the vegetation. However, the soils which are shallow, coarse-textured, stony, liable to heavy erosion or with hard compact laterite sub-soil and possess low moisture and nutrient status, carry semi-evergreen forest often without Dipterocarpus indicus. The deep clayey fertile soils with good drainage and adequate moisture supply favour evergreen forest with D. indicus and such other species. On the other hand, deep sandy soil in a valley with somewhat high water table support evergreen forest dominated by Vateria indica, whereas the soil having swampy sub-soil is occupied by Myristica swamp forest. The necessity for conducting more intensified soil studies and for taking utmost care in carrying out heavy working in these forests has been indicated.